Psychiatric treatment: in the absence of law?: R (on the application of B) v. Ashworth Hospital Authority and another, [2005] U.K.H.L. 20 - Bartlett, Peter (Oxford University Press, 2006)
This case concerns the scope of the compulsory treatment provisions of the Mental Health Act 1983. In particular, it determines whether persons confined under that Act may be compulsorily treated for any mental disorder or only for the form of mental disorder justifying their confinement.